The Influence of Traditional Birth Attendants' Role on Delivery Decisions by Pregnant Women (International Forum of Researchers and Lecturers, 2025)
Background: Traditional birth attendants (TBAs) still play a crucial role in pregnancy and childbirth in Indonesia. Public trust in TBAs often influences pregnant women's decisions regarding where to deliver. Objective: To analyze the influence of the role of TBAs on birth decisions by pregnant women. Methods: A quantitative cross-sectional study was conducted among 92 postpartum mothers in Sukamurni Village. Data were collected using a questionnaire and analyzed using a chi-square test. Results: Thirty-seven percent of respondents chose non-medical delivery. The chi-square test showed a significant correlation between the role of TBAs and birth decisions (p = 0.000). Conclusion: TBAs significantly influence pregnant women's birth decisions. An integrative strategy is needed between health workers and TBAs in culture-based health services.